Study of Aluminum-Copper Electrodes for Chromium and Chemical Oxygen Demand Removal from Tannery Wastewater by Electrocoagulation - Rivaldi, Mochammad Heldry; Rizky, Amelia; Hardian, Arie; Murniati, Anceu (Jurnal Riset Kimia, 2025)
This study investigates the efficacy of the electrocoagulation (EC) process using aluminum (Al) anodes and cathodes for the treatment of leather tanning wastewater. Initial characterization revealed a chemical oxygen demand (COD) of 901.96 mg/L and total chromium content of 38.741 mg/L, where it exceeds the discharge limit permitted by the Minister of Environment Regulation No. 5/2014, the permissible limit for COD in industrial wastewater is 110 mg/L, and for total chromium, it is 0.6 mg/L. The EC process, conducted under varying conditions of electrolysis time (10, 20, and 30 minutes), potential (2.0, 3.0, 3.5, and 4.5 V), and current intensity (1.0, 2.0, and 3.0 A), demonstrated substantial reductions in both COD and chromium levels. The lowest COD value achieved was 28.05 mg/L at 3A, 4.5 V, and 30 minutes, representing a reduction of 52.09% to 74.50%. Total chromium content was reduced to as low as 0.013 mg/L, indicating a reduction of 90.45% to 97.83%. pH levels were monitored, revealing an increase due to OH- ion formation, with final pH values ranging from 6.38 to 8.34. XRF analysis of the commercial Al anode indicated a composition of 98.1% Al, 0.615% Fe, 0.522% Si, and 0.163% Zn. The findings underscore the effectiveness of the EC process in reducing COD and chromium content in leather tanning wastewater, meeting and exceeding regulatory standards.